CAEP Position Statement – Sick notes for minor illness. Issue 4 (July 2020) - McLaren, Jesse; Hayman, Kate; Sheikh, Hasan
Abstract : Employer- and school-mandated verification of minor illness leads patients to use healthcare resources solely to obtain a "sick note." This puts unnecessary strain on the patient and the emergency department (ED), and threatens to spread communicable diseases in our community.